2014
DOI: 10.18553/jmcp.2014.20.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of Saxagliptin in Patients with Inadequately Controlled Type 2 Diabetes: Results from 6 Phase III Studies

Abstract: BACKGROUND: Oral antihyperglycemic drugs used to treat type 2 diabetes mellitus (T2DM) vary in safety and tolerability. Treatment-related hypoglycemia and weight gain can exacerbate underlying disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Pooled data from six phase 3 clinical trials reported no significant increase in confirmed hypoglycemic events for both 2.5 and 5mg of saxagliptin compared to placebo, 0.8%, 0.5% and 0.4% respectively [38]. As an add-on therapy over 24 weeks, similar results were demonstrated [38]. The frequency of confirmed hypoglycemic events was 0% for initial combination therapy with metformin compared to 0.3% with metformin alone.…”
Section: Safety and Tolerabilitymentioning
confidence: 75%
See 4 more Smart Citations
“…Pooled data from six phase 3 clinical trials reported no significant increase in confirmed hypoglycemic events for both 2.5 and 5mg of saxagliptin compared to placebo, 0.8%, 0.5% and 0.4% respectively [38]. As an add-on therapy over 24 weeks, similar results were demonstrated [38]. The frequency of confirmed hypoglycemic events was 0% for initial combination therapy with metformin compared to 0.3% with metformin alone.…”
Section: Safety and Tolerabilitymentioning
confidence: 75%
“…The lower risk of hypoglycaemia is related to its glucose-dependant mechanism of action. Pooled data from six phase 3 clinical trials reported no significant increase in confirmed hypoglycemic events for both 2.5 and 5mg of saxagliptin compared to placebo, 0.8%, 0.5% and 0.4% respectively [38]. As an add-on therapy over 24 weeks, similar results were demonstrated [38].…”
Section: Safety and Tolerabilitymentioning
confidence: 85%
See 3 more Smart Citations